A Serious Game Employed to Introduce Principles of Interprofessional Collaboration to Students of Multiple Health Professions. (June 2022) - Fusco, Nicholas M.; Jacobsen, Lisa Jane; Klem, Nicole; Krzyzanowicz, Ryan; Ohtake, Patricia J.
Background: Serious games may be beneficial to student learning and skill development when deployed within the context of interprofessional education (IPE). The purpose of this study was to describe the development, implementation, and evaluation of a serious game to introduce foundational knowledge and skills related to interprofessional collaboration in health professions education. Methods: A commercially available board game simulation product was purchased by the university and was central to this learning experience. Participants included students from 13 professional programs. During each session, students were organized into teams of four, engaged in an open discussion with their team, played the game and participated in debriefing. At the conclusion, students completed an 11-item program evaluation. Frequencies for each forced-rating question were reported in aggerate and analyzed by profession. A thematic analysis was conducted for open-ended questions. Results: A total of 229 students participated and completed the program evaluation. Greater than 88% of respondents either "Agree" or "Strongly Agree" that after participating they were able to communicate and collaborate with students from other health professions programs; discuss the roles of collaboration, innovation, and being data-driven for health-systems improvement; and discuss the importance of teamwork in healthcare provision. Respondents reported this experience contributed to their competence as an interprofessional team member in the areas of teamwork, communication, and creative problem solving. Conclusions: An interprofessional serious game was well-rated by a diverse group of health professions students. Students reported a high level of agreement with being able to discuss concepts important to interprofessional collaboration.